Artificial Intelligence as a Bridge Between Islamic Knowledge and English Language Learning (Journal of Pedagogical Inventions and Practices, 2026)
This chapter explores the transformative potential of Artificial Intelligence (AI) in bridging Islamic knowledge acquisition with English Language Learning (ELL), conceptualizing AI as an interdisciplinary learning tool. It synthesizes current applications of AI in both Islamic education and ELL, highlighting AI's capabilities in personalization, adaptive feedback, and content delivery. The analysis reveals that AI can facilitate the integration of Islamic texts and concepts into tailored ELL curricula, thereby enhancing accessibility, engagement, and cultural relevance for learners. However, the chapter critically evaluates challenges such as the necessity of human pedagogical oversight for ethical and spiritual development, and the complexities of Natural Language Processing (NLP) for Arabic texts. The proposed conceptual framework emphasizes a complementary role for AI, augmenting human instruction and fostering a dynamic, culturally situated learning environment.